3D models related to the publication: A new primate community from the earliest Oligocene of the Atlantic margin of Northwest Africa: Systematic, paleobiogeographic and paleoenvironmental implications - (:unkn) unknown (My University, 2024)
This contribution contains the three-dimensional digital models of the dental fossil material of anthropoid and strepsirrhine primates, discovered in Lower Oligocene detrital deposits outcropping in the Porto Rico and El Argoub areas, east of the Dakhla peninsula region (Atlantic Sahara; in the south of Morocco, near the northern border of Mauritania). These fossils were described, figured and discussed in the following publication: Marivaux et al. (2024), A new primate community from the earliest Oligocene of the Atlantic margin of Northwest Africa: Systematic, paleobiogeographic and paleoenvironmental implications. Journal of Human Evolution 193, e103548. https://doi.org/10.1016/j.jhevol.2024.103548
Keywords: African Research